PROSPECTS FOR IMPROVING EMPLOYMENT COMPOSITION AND INCREASE EFFICIENCY IN THE NATIONAL ECONOMY (American Journal of Business Management, Economics and Banking, 2024)
The article is devoted to employment issues and the economic essence of effective employment, one of the most important indicators of intellectual capital, taking into account the specifics of labor and real structural changes in the economy. In addition, issues such as the criteria for establishing effective employment between the employer, employee, government and enterprise, as well as issues of the professional level of the employee are considered.